2015
DOI: 10.1007/s11187-015-9642-4
|View full text |Cite
|
Sign up to set email alerts
|

ADHD-like behavior and entrepreneurial intentions

Abstract: Little is known about the relation between entrepreneurship and the extent of psychiatric symptoms. Validated psychiatric symptom scores are seldom used for non-clinical reasons. One prevalent symptom that deserves our interest is Attention Deficit and Hyperactivity Disorder (ADHD). ADHD is a developmental disorder characterized by inattentiveness and hyperactivity that has been linked to occupational choice and performance. Building on the person-environment fit literature, we hypothesize that individuals who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
137
3
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(154 citation statements)
references
References 111 publications
(131 reference statements)
8
137
3
6
Order By: Relevance
“…Even though studies have not yielded consistent evidence, it can be argued that after adolescence risk aversion decreases with age (Cutler 1995;Hallahan et al 2004;Wang and Hanna 1997). Assuming that risk tolerance influences entrepreneurship (Block et al 2015;Caliendo et al 2014;Karlsson and Warda 2014;Nieß and Biemann 2014;Verheul et al 2015), this argument can explain the above result. However, research on risk aversion and entrepreneurship has revealed conflicting results (Miner and Raju 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Even though studies have not yielded consistent evidence, it can be argued that after adolescence risk aversion decreases with age (Cutler 1995;Hallahan et al 2004;Wang and Hanna 1997). Assuming that risk tolerance influences entrepreneurship (Block et al 2015;Caliendo et al 2014;Karlsson and Warda 2014;Nieß and Biemann 2014;Verheul et al 2015), this argument can explain the above result. However, research on risk aversion and entrepreneurship has revealed conflicting results (Miner and Raju 2004).…”
Section: Discussionmentioning
confidence: 99%
“…A study of 306 French entrepreneurs found that those with ADHD symptoms had elevated entrepreneurial orientation ), a predictor of small firm survival and growth (Rauch et al 2009). A study of 10,000 Dutch university students found that those with ADHD-like behavior had higher entrepreneurial career intentions compared to the others (Verheul et al 2015.…”
Section: Adhdmentioning
confidence: 99%
“…However, there is substantial variability in individual abilities, disability, and functional outcomes. For example, limited research suggests specific strengths related to ADHD, including sense of entrepreneurship [16] and innovative thinking [17]. The interindividual differences in functioning can be influenced by personal factors (e.g., self-esteem and self-efficacy) [18], participation in skill training programs [19], pharmacological treatments [20], and degree of family support [21], among others.…”
Section: Introductionmentioning
confidence: 99%